Analisis Prespektif Hukum Terhadap Permohonan Pengesahan Nikah Poligami Sirri - Salsabila Haura Yusdika (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The act of marriage due to infidelity that is not officially registered can lead to legal issues, including marriages that are not illegal but not properly registered, marriages that are not fully in accordance with the law, and marriages that violate the law and religious beliefs. The main legal issue arising from this phenomenon is that, according to Article 4 and 9 of the Marriage Law, a man who wants to have more than one wife must apply to the court for permission. The implementation of isbat nikah for secret polygamy has its advantages and disadvantages. Researchers used qualitative descriptive research analysis with normative juridical research methodology. The research findings indicate that, in a positive light, practitioners of secret polygamy can obtain a marriage certificate and are obliged to obtain legal protection for their marriage, which can improve their social status, change their lineage status, and give them legal claims to joint property and inheritance. However, on the negative side, if secret polygamy is approved, it implies that individuals who have violated the law are forgiven and justified, and the regulations governing polygamy requirements are emphasized in terms of value. As a result, the Supreme Court no longer approves secret polygamous marriages based on SEMA No. 3/2018.